Pengaruh Struktur Modal, Profitabilitas, dan Biaya Operasional Terhadap Pajak Penghasilan Badan Terutang Pada Perusahaan Sub Sektor Pertambangan Periode 2023 - 2024: The Effect of Capital Structure, Profitability, and Operating Costs on Corporate Income Tax Payable in Mining Sub-Sector Companies for the 2023 - 2024 Period - Anggita Riski Dwi Lestari; Ninuk Riesmiyantiningtias; Woro Dwi Hartanty (CV Warnak Johanna Nusantara, 2026)
The financial statements of the mining sector show fluctuations in corporate income tax payable, with a decrease of 6.72% in 2023 and an increase of 4.89% in 2024. This study aims to analyze the effect of capital structure, profitability, and operating expenses on corporate income tax payable in mining companies listed on the Indonesia Stock Exchange for the 2023–2024 period. The approach used is descriptive quantitative, focusing on numerical data analysis using statistical methods. According to (Salsabila, 2024) the quantitative method upholds the validity and reliability of data and is able to limit phenomena into objectively measurable variables. Hypothesis testing was conducted using SPSS version 25. The results of the study show that Ha is accepted and Ho is rejected, indicating that the three independent variables have a significant effect on corporate income tax payable. In conclusion, capital structure, profitability, and operating expenses collectively influence the amount of tax that must be paid by mining companies.